Lightning strike damage resistance of carbon‐fiber composites with nanocarbon‐modified epoxy matrices. Issue 46 (30th September 2022) - Kopsidas, Sotirios; Olowojoba, Ganiu B.; Stone, Chris; Clark, David; Haddad, A. Manu; Kinloch, Anthony J.; Taylor, Ambrose C.
Abstract: Carbon‐fiber reinforced polymer (CFRP) composites are replacing metal alloys in aerospace structures, but they can be vulnerable to lightning strike damage if not adequately protected due to the poor electrical conductivity of the polymeric matrix. In the present work, to improve the conductivity of the CFRP, two electrically conductive epoxy formulations were developed via the addition of 0.5 wt% of graphene nanoplatelets (GNPs) and a hybrid of 0.5 wt% of GNPs/carbon nanotubes (CNTs) at an 8:2 mass ratio. Unidirectional CFRP laminates were manufactured using resin‐infusion under flexible tooling (RIFT) and wet lay‐up (WL) processes, and subjected to simulated lightning strike tests. The electrical performance of the RIFT plates was far superior to that of the WL plates, independent of matrix modification, due to their greater carbon‐fiber volume fraction. The GNP‐modified panel made using RIFT demonstrated an electrical conductivity value of 8 S/cm. After the lightning strike test, the CFRP panel remains largely unaffected as no perforation occurs. Damage is limited to matrix degradation within the top ply at the point of impact and localized charring of the surface. The GNP‐modified panel showed a comparable level of resistance against lightning damage with the existing copper mesh technology, offering at the same time a 20% reduction in the structural weight. This indicates a feasible route to improve the lightning strike damage resistance of carbon‐fiber composites without the addition of extra weight, hence reducing fuel consumption but not safety. Abstract : Carbon‐fiber reinforced polymer (CFRP) structures are inherently prone to damage from lightning strikes, due to the electrically insulating nature of the epoxy matrix. The electrical conductivity of epoxies can be significantly enhanced through the incorporation of graphene nanoplatelets (GNPs). A CFRP panel manufactured using a GNP‐modified epoxy can withstand the impact of 40 kA lighting current, demonstrating a noticeable damage tolerance improvement compared to its unmodified counterpart.